2019
DOI: 10.1155/2019/3917393
|View full text |Cite
|
Sign up to set email alerts
|

Medical Application of Hydrogen in Hematological Diseases

Abstract: Hydrogen gas has been reported to have medical efficacy since the 1880s. Still, medical researchers did not pay much attention to hydrogen gas until the 20th century. Recent research, both basic and clinical, has proven that hydrogen is an important physiological regulatory factor with antioxidative, anti-inflammatory, and antiapoptotic effects. In the past two decades, more than 1000 papers have been published on the topic, including organ ischemia-reperfusion injury, radiation injury, diabetes, atheroscleros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…We believe that if the administration time is extended, the overall response rate will still rise. Thirdly, the hydrogen molecule is very small, has a strong penetration ability, can quickly penetrate the biofilm, and reach a higher concentration in the cell to play a therapeutic role ( 24 ). Finally, H 2 is cheap and easy to obtain.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that if the administration time is extended, the overall response rate will still rise. Thirdly, the hydrogen molecule is very small, has a strong penetration ability, can quickly penetrate the biofilm, and reach a higher concentration in the cell to play a therapeutic role ( 24 ). Finally, H 2 is cheap and easy to obtain.…”
Section: Discussionmentioning
confidence: 99%
“…Thanks to this discovery, hydrogen gas has been used in 300 diseases and have come to the forefront of therapeutic medical gas research. Clinical research has shown that hydrogen is an essential physiological regulator factor with anti-inflammatory and antioxidant effects on cells and organs [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen (H 2 ) is the oldest and simplest molecule in our Universe. It can protect a variety of organ injuries as well due to its antioxidation, anti-inflammatory, and antiapoptotic effects [12,13]. Interestingly, H 2 has a remarkable therapeutic effect on various diseases, including organ ischemiareperfusion injury and sepsis [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Molecular hydrogen was previously taken as an inert gas into account, while a research reported that it has antioxidant, anti-inflammatory, and antiapoptotic properties, with organ protection for a variety of acute and chronic diseases [12,13]. In an animal model of intestinal I/R injury, H 2 can simultaneously reduce local intestinal damage and distant organs damage [12,18,19].…”
mentioning
confidence: 99%